Botswana : 2006 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities for Botswana. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the 2006 Article IV Consultation on Botswana highlights economic developments and monetary and exchange rate policy. Botswana's growth has been fueled by continued increases in diamond production; and real diamond output is projected to level off, and then decline sharply after about 15 years. Diversification of the economy will require implementation of substantial structural reforms, in particular the authorities' planned reforms in labor markets, the investment environment, and the role of parastatals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet